Histopathological study of Trygon zugei infected with tapeworm from Ratnagiri district (M.S.) India. - Anarse, Sandeep; Borde, Sunita; Humbe, Atul (International Multidisciplinary Research Journal, 2012)
The marine water fish trygon zugei collected from Ratnagiri district during the period of June 2009 to may 2010. After dissection their intestinal passage was examined for tapeworm parasite. The tapeworm, tetragonocephalum sp. Shipley (1905). The histopathological studies were carried out and observation clearly shows that the parasite, Tetragonocephalum sp. was approaching to the intestinal villi, embedded in the fibroblast cell and is attached to the intestinal villi. The histopathological studies of tapeworm Tetragonocephalum sp. have been studied to find the pathological changes and extend of damage of the intestinal layers of trygon zugei.